The role of tourism in the global economy - Oveskov, O. V. (My University, 2021)
The relevance of this topic lies in the fact that tourism greatly affects the development of the economy of any country. The tourist potential of various states is a very difficult concept, difficult for an unambiguous interpretation and assessment. This fact largely depends on the service level which tourists are used to, there are objects of cultural, natural, and historical heritage of each particular state, different in origin and essence. At the same time, several external factors of the political, economic, cultural, social, and psychological nature represent significant influence on the indicators of the attractiveness degree for the mentioned above tourists’ orientation.
Keywords: tourism; economy; international tourism; tourism sector; travelling; revenues